Ligand design strategies to increase stability of gadolinium-based magnetic resonance imaging contrast agents - Thomas J. Clough (Nature Portfolio, 2019)
Gadolinium(III) complexes are strong enhancers of magnetic resonance imaging (MRI) signals, thus are widely used as contrast agents despite their potential toxicity. Here, the authors review ligand design approaches aimed at improving the stability of Gd(III)-based MRI contrast agents.